Integrating Congruence Geometry in Strengthening Numeracy Among Junior High School Students: A Case Study - Nurhayati, Elis; Abadi , Agus Maman; Wijaya, Ariyadi (International Journal of Geometry Research and Inventions in Education, 2025)
This study examined the effectiveness of integrating congruence geometry into contextual numeracy learning to enhance junior high school students’ mathematical reasoning. A qualitative case study with quantitative support was conducted with 32 eighth-grade students and one mathematics teacher at a public school in West Java, Indonesia. The intervention included eight lessons embedding geometric transformations—reflection, rotation, and translation—into culturally relevant numeracy tasks such as batik and tiling designs. Data were collected through pretests, posttests, classroom observations, and interviews. Results showed a 43% improvement in contextual numeracy indicators and a significant increase in students’ ability to recognize congruent shapes, explain geometric reasoning, and apply transformations to real-life problems (t(31) = 6.42, p < 0.001). Observational and interview data revealed greater engagement, collaboration, and reduced mathematics anxiety. Findings support the four-dimensional numeracy framework (Goos et al., 2014) and Battista’s theory of geometric reasoning (2007), emphasizing that contextual and culturally grounded tasks foster conceptual understanding and motivation. The study concludes that contextualized geometry-based numeracy instruction effectively promotes students’ understanding, transfer of learning, and confidence, offering implications for developing culturally responsive mathematics curricula.